Symmetry Two-axis Tilt Angle Capacitive Sensor System - Tran, Thi Thuy Ha (H. : ĐHQGHN, 2019)
This paper presents the design, fabrication and operation of a highly symmetrical two-axis capacitive sensor. The proposed sensor consists of five electrodes, including of an excitation electrode and two pairs of sensing electrodes with exactly the same dimensions, arranged at identified symmetrically locations on a 3D printed hollow sphere, which containing dielectric medium formed by the partly filled oil and the remaining air. The proposed sensor can measure the tilt angle about the x-axis and y-axis with symmetrical outputs. The proposed sensor is fabricated using a rapid prototyping technology and mounted on the surface of a printed circuit board (PCB) for mechanical packaging and signal processing. Experimental measurement results show that the sensor system can measure the tilt angle in both the x- and y-axis with sensitivity of 103 mV/degree and resolution of ±1 degree in the range of -30 degree to +30 degree. This sensor system can be used in many military and consumer applications.